Forest Management in the Interface: Practicing Visible Stewardship - Bruce Hull; Sarah F. Ashton; Rien M. Visser; Martha C. Monroe (EDIS)
Revised! FOR-177, a 4-page fact sheet by Bruce Hull, Sarah F. Ashton, Rien M. Visser, and Martha C. Monroe, reviews a suite of visible stewardship options, such as cues-to-care and screening practices that can help improve public perceptions of resource management practices such as timber harvesting. Includes references. Published by the UF School of Forest Resources and Conservation, July 2008.